Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1063/1.4974948
|View full text |Cite
|
Sign up to set email alerts
|

Small polaron hopping conduction mechanism in LiFePO4 glass and crystal

Abstract: The optimization of a cathode material is the most important criterion of lithium ion battery technology, which decides the power density. In order to improve the rate capability, a cathode material must possess high electronic and ionic conductivities. Therefore, it is important to understand the charge transport mechanism in such an advanced cathode material in its intrinsic state before modifying it by various means. In this work, we report the thermal, structural, and electrical conductivity studies on lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…It is well-known that above room temperature conduction in iron phosphate-based glasses is due to phonon-assisted hopping of polarons between nearest neighboring sites [1][2][3][4][5][6][7] and the DC conductivity is thermally activated with characteristic activation energy. The temperature dependence of DC conductivity, σ DC , in this temperature range is usually expressed by Austin-Mott's relation [1,2,5]:…”
Section: Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that above room temperature conduction in iron phosphate-based glasses is due to phonon-assisted hopping of polarons between nearest neighboring sites [1][2][3][4][5][6][7] and the DC conductivity is thermally activated with characteristic activation energy. The temperature dependence of DC conductivity, σ DC , in this temperature range is usually expressed by Austin-Mott's relation [1,2,5]:…”
Section: Conductivitymentioning
confidence: 99%
“…Iron phosphate-based glasses belong to a family of electronically conducting materials in which the conduction mechanism follows the small polaron hopping theory [1][2][3][4][5][6][7]. The polaronic conductivity in these glasses originates from the electron transfer between ferric and ferrous ions and, consequently, shows a strong dependence on the total amount of iron oxide, fraction of ferrous/ferric ions and average distance between them.…”
Section: Introductionmentioning
confidence: 99%
“…Austin and Mott proposed a detailed theoretical approach to the conduction process and activation energy of transition metal oxide (TMO) glasses with their model [24,25]. As is well known, conduction in IPGbased glasses at temperatures above RT is considered as phonon-assisted small polaron hopping (SPH) between local neighboring sites [30,[36][37][38]57,58] and the DC conductivity exhibits an Arrhenius temperature dependence with characteristic activation energy. The temperature dependence of DC conductivity, σ DC , is usually expressed by the Austin-Mott relation [36,37,57]:…”
Section: Impedance Spectra and Direct Current (Dc) Conductivitymentioning
confidence: 99%
“…The electric conductivity showed that LFPG exhibited a higher polaronic conductivity of 1.6 orders than the LFPC sample. The investigations revealed that the enhancement of polaronic conductivity in LFPG is attributed to the combined effect of the reduced hopping length, decreased activation energy, and the enhanced polaron concentration [154] .…”
Section: Olivine Phosphate 241 Introductionmentioning
confidence: 99%